SAT0316 Neurological Involvement in Patients with Antiphospholipid Syndrome: A Case Series with A Long-Term Follow-Up. (15th July 2016) - Estévez, M.; Argibay, A.; Pérez, A.; Vázquez-Triñanes, C.; Machado, B.; Lorenzo, R.; Sousa, A.; Villaverde, I.; Freire, M.; Rivera, A.
Abstract : Background: Antiphospholipid syndrome (APS) is a systemic autoimmune disorder characterized by autoantibody production and thrombosis or pregnancy morbidity. Central nervous system abnormalities are a common feature of APS that have been attributed to both vascular thrombosis as well as direct injury to neuronal tissue by antiphospholipid antibodies. Neurological manifestations in APS are diverse and may be confused with other neurologic syndromes. Objectives: The aim of our study was to determine the prevalence and the type of neurological involvement in patients with APS. Methods: A case series of patients with APS diagnosed and followed for a long period in a specific unit of Thrombosis and Vasculitis was conducted. Clinical and laboratory data were collected in a retrospective manner. Patients with neurological manifestations were compared with patients without nervous system involvement. Chi2 and t-student were used, using the statistical package SPSS22.0. Results: 88 patients with APS were included, 63 (71, 6%) female, mean age 56, 5 ± 20 years [range 11–89], with a mean follow-up of 9, 1 years (median 7 years). 23 patients (26, 1%) had a secondary APS: 20 SLE, 2 systemic sclerosis and 1 Sjögren's syndrome. 4 (4, 5%) were pure obstetric APS, 36 (40, 9%) had an arterial thrombosis, 30 (34, 1%) had a venous thrombosis and 18 (20, 4%) had mixed events (arterial, venous and obstetric). 60 (68, 2%) patients had a cardiovascular risk factor (hypertension, dyslipidemia, type 2 DM) and 15 (17%) had atrial fibrillation. 49 patients of 88 with APS (55, 7%) had neurological involvement. 26 (53, 1%) patients had ischemic stroke, 8 (16, 3%) transient ischemic attack, 16 (32, 6%) cognitive deficits, 14 (28, 6%) epilepsy, 8 (16, 3%) headache, 5 (10, 2%) psychosis, 7 (14, 3%) movement disorders and 3 (6, 1%) had sensorineural hearing loss. 28 (31, 8%) patients had ≥2 neurologic symptoms. 19 patients (38, 8%) had white matter lesions on MRI but only 1 patient was diagnosed with multiple sclerosis. In 17 patients (34, 7%) neurological involvement was diagnosed before APS (mean 7, 2 ± 7, 9 years). Only 3 patients had livedo reticularis: 2 SLE y 1 Sneddon syndrome. No significant differences in age, sex, classification, antiphospholipid antibodies, comorbidities and therapy were observed between patients with or without neurological manifestations. Hospitalization (93, 9% vs 74, 4%, p 0, 01) and mortality (36, 7% vs 7, 7%, p 0, 001) was higher in neurological APS. Conclusions: More than half of patients with APS had neurological involvement. Cerebrovascular ischemic events and cognitive deficits were the most common manifestations. Neurological involvement was associated with higher mortality and hospitalization. Neurological symptoms may occur long before diagnosis of APS. We have not identified risk markers of central nervous system involvement. References: Arnson Y et al. The antiphospholipid syndrome as a neurological disease. Semin Arthritis Rheum. 2010;40(2):97. Muscal E, Brey RL. Neurologic manifestations of the antiphospholipid syndrome: integrating molecular and clinical lessons. Curr Rheumatol Rep. 2008;10(1):67. Disclosure of Interest: None declared